Rancang Bangun Prototipe Alat Ukur Kecepatan dan Arah Angin Berbasis Arduino Pro Mini Studi Kasus Penerapan pada Olahraga Paralayang di Parangtritis - Tony Yulianto; Arief Ikhwan Wicaksono; Netania Indi Kusumaningtyas (Fakultas Teknik dan Teknologi Informasi, Universitas Jenderal Achmad Yani Yogyakarta, 2020)
Wind is a phenomenon observable a mass movement of air the effect and experienced in everyday life due to differences in the air pressure in two separate places so there the airflow from a having the air pressure is higher to a lower have pressure air. Fast slowness wind speed depends on how big a pressure difference of the two it. Essentially any need sports facilities must meet the standard sports itself. Sports paralayang, on the need facilities able to meet a need the related sports development. This study aims to to build a helmet safety to users paralayang on sports paralayang in parangritis. A helmet these were designed based microcontroller to help users paralayang, so users of paralayang would quickly get information that can be used as an effort to safety. The helmet worn by paralayang, which in upon the helmet these there were instrument that serves to measuring wind speed. When the wind is fast , this instrument will sound and paralayang must be down. So risk can minimize accident. The result of this study graphic display the output of a system for conducting the process of wind measurements is expected to measuring changes wind is more precision by means of sensors optocoupler which are cheap and have good qualities.